Calculus of Finite Differences Part-1

Calculus of Finite Differences Part-1

Achyut Bharadwaj, Saee Patil, Valentio Iverson, Danny Li
August 2021
calculus, finite difference, sequences, patterns, polynomials, chain rule

Acknowledgements #

This work was carried out as part of a research project at PROMYS-2021. I am a grateful recipient of the Mehta Fellowship to the PROMYS programs in 2021 and 2022.

Preliminary Definitions #

Finding Patterns #

(1) $$1,4,7,10,\cdots\;\;?$$

Here’s a harder one:

(2) $$3,4,6,9,13,\cdots\;\;?$$

Notations #

(3) $$\Delta\left(f\right)(x)=f(x+1)-f(x)$$
(4) $$\Delta^{n+1}(f)=\Delta\left(\Delta^n(f)\right)$$

What is $\Delta\left(f\right)$ when $f$ is $1,4,7,10,\cdots$?

What is $\Delta\left(f\right)$ when $f$ is $3,4,6,9,13\cdots$?

What is $\Delta^2(f)$ when $f$ is $3,4,6,9,13\cdots$?

Some Results #

$\Delta\left(f\right)$ is a polynomial iff $f$ is a polynomial.

(5) $$\Delta^n(f)=c\Rightarrow \Delta^{n+1}(f)=0$$

Let

(6) $$f(x)=a_mx^m+a_{m-1}x^{m-1}+\cdots+a_1x+a_0,a_m\neq0$$
The least $n$ such that $\Delta^n(f)=0$ is $m+1$.

$\Delta^{-1}$ #

We define $\Delta^{-1}(f(x))$ as a function $g(x)$ such that $\Delta\left(g(x)\right) = f(x)$.

Patterns again! #

(7) $$1^2 + 2^2 + 3^2 + \cdots + (n-1)^2 = ~?$$
What about
(8) $$1^3 + 2^3 + \cdots + (n-1)^3 = ~?$$
Can you find
(9) $$\sum_{i=0}^{n-1} i^k$$
recursively?

Generalizing #

Observe that

(10) $$\sum_{i=0}^{n-1}(i+1)^k - \sum_{i=0}^{n-1}i^k = n^k$$
So,
(11) $$\sum_{i=0}^{n-1}(i+1)^k - i^k = n^k$$

The above becomes:

(12) $$\sum_{i=0}^{n-1}\sum_{j=1}^{k}\binom{k}{j}i^{k-j} = \sum_{i=0}^{n-1}(ki^{k-1} + \sum_{j=2}^{k}\binom{k}{j}i^{k-j}) = n^k$$
using the binomial theorem.

So, we have

(13) $$n^k-\sum_{i=0}^{n-1}(\sum_{j=2}^{k}\binom{k}{j}i^{k-j}) = k\sum_{i=0}^{n-1}i^{k}$$
by rearranging the above.

Hence,

(14) $$\sum_{i=0}^{n-1}i^k = \frac{n^k - \sum_{i=0}^{n-1}(\sum_{j=2}^{k}(\binom{k}{j}i^{k-j}))}{k}$$

Calculus vs Finite Differences #

Addition and multiplication under a finite difference #

(15) $$\Delta\left(f(x)+g(x)\right) = \Delta\left(f(x)\right)+\Delta\left(g(x)\right)$$
(16) $$\begin{aligned}\Delta\left(f(x)+g(x)\right) &= (f(x+1)+g(x+1)) - (f(x)+g(x)) \\ &= (f(x+1)-f(x)) + g(x+1) - g(x) \\ &= \Delta\left(f(x)\right) + \Delta\left(g(x)\right)\end{aligned}$$

Multiplication of finite difference #

We now try to find a generic formula for the product of two functions under a finite difference.

(17) $$\Delta\left(f(x)\cdot g(x)\right) = f(x+1)\Delta\left(g(x)\right) + g(x)\Delta\left(f(x)\right)$$

(18) $$\Delta\left(f(x)\cdot g(x)\right) = f(x+1)g(x+1) - f(x)g(x)$$
We add and subtract $g(x)f(x+1)$ in the above to get:
(19) $$\begin{aligned} \Delta\left(f\cdot g\right) &= f(x+1)g(x+1) - f(x)g(x) + f(x+1)g(x) - f(x+1)g(x) \\ &= f(x+1)(g(x+1) - g(x)) + g(x)(f(x+1)-f(x)) \\ &= f(x+1)\Delta\left(g(x)\right) + g(x)\Delta\left(f(x)\right) \end{aligned}$$

Division under a finite difference #

Before trying to find a formula for division, we try to find one for the multiplicative inverse, i.e. finding $\Delta\left(\frac{1}{f(x)}\right)$ in terms of $f(x)$

(20) $$\Delta\left(\frac{1}{f(x)}\right) = \frac{1}{f(x+1)} - \frac{1}{f(x)} = \frac{f(x)-f(x+1)}{f(x+1)f(x)} = -\frac{\Delta\left(f(x)\right)}{f(x+1)f(x)}$$
Now,
(21) $$\Delta\left(\frac{f(x)}{g(x)}\right) = \Delta\left(f(x)\cdot\frac{1}{g(x)}\right) = f(x+1)\Delta\left(\frac{1}{g(x)}\right) + \frac{1}{g(x)}\Delta\left(f(x)\right)$$
by the product formula. The above can be written as:
(22) $$-f(x+1)\frac{\Delta\left(g(x)\right)}{g(x+1)g(x)} + \frac{\Delta\left(f(x)\right)}{g(x)} = \frac{g(x+1)\Delta\left(f(x)\right)-f(x+1)\Delta\left(g(x)\right)}{g(x+1)g(x)}$$

Chain Rule #

Evaluate $\Delta\left(f(x)\right)$ when $f(x)=(2x)^2$

$(2x)^2 = 4x^2$. Now, $\Delta\left(4x^2\right) = 4\Delta\left(x^2\right) = 4(2x+1) = 8x+4$.

We compare this with the calculus chain rule. Is it possible to let $u=2x$, find $\Delta\left(f(u)\right)$, and multiply it by $\Delta u$ to get the result as we do in calculus?

(23) $$f(u)=u^2 \implies \Delta f(u) = 2u + 1 = 4x + 1$$
Also, $\Delta u = 2$. So,
(24) $$\Delta f(u)\cdot \Delta u = (4x+1)\times2 = 8x + 2 \neq 8x+4$$
We explore why it does not work in the next few slides.

We think of the function $\Delta$ as finding the slope of a curve between two integral points.

Chain Rule
Fig-1: Chain Rule

So, we can conclude that

(25) $$\Delta\left((f)(x)\right) = \frac{\Delta\left(f(x)\right)}{\Delta x}$$

We need

(26) $$\frac{\Delta f}{\Delta g}\cdot\frac{\Delta g}{\Delta x} = f(g(x))\Delta\left(g(x)\right)$$
for the chain rule to work.

We know that

(27) $$\frac{\Delta g(x)}{\Delta x} = \Delta g(x)$$
from the graph in Fig-1. Hence, we need
(28) $$\frac{\Delta f(x)}{\Delta g(x)} = f(g(x))$$
for the chain rule to work. This however does not hold true for every $f(x),g(x)$ as we saw in the example.

In calculus however, the difference is not finite. Hence, the above holds.

Some fun with $\Delta^{-1}$ #

Find $\Delta^{-1}(x + 1)$. Can you find $\Delta^{-1}(f(x)+g(x))$ in terms of $f(x),g(x)$?

We know

(29) $$\Delta^{-1}(2x+1) = x^2+c$$
. Also,
(30) $$\Delta^{-1}x = \frac{x^2-x}{2}+c$$
So, one can guess that
(31) $$\Delta^{-1}(2x+1) = x^2 - \frac{x^2-x}{2} = \frac{x^2 + x}{2}+c$$
for some constant $c$. Indeed, we can check to see that this is true!   Notice that this is the same as
(32) $$\Delta^{-1}(x) + \Delta^{-1}(1)$$
This leads to a proposition.

Addition under $\Delta^{-1}$ #

(33) $$\Delta^{-1}(f+g) = \Delta^{-1}(f)+\Delta^{-1}(g)$$
for all $f,g$ whose differences are defined.

We know that

(34) $$\Delta\left(f'+g'\right) = \Delta\left(f'\right)+\Delta\left(g'\right)$$
Now,
(35) $$\Delta^{-1}(\Delta\left(f'+g'\right)) = f'+g'$$
Hence,
(36) $$\Delta^{-1}(\Delta\left(f'\right)+\Delta\left(g'\right))=f'+g'$$

Also,

(37) $$\Delta^{-1}(\Delta\left(f'\right)) + \Delta^{-1}(\Delta\left(g'\right)) = f' + g'$$

Equating the LHS of the above two equations, we get:

(38) $$\Delta^{-1}(\Delta\left(f'\right)+\Delta\left(g'\right))=\Delta^{-1}(\Delta\left(f'\right)) + \Delta^{-1}(\Delta\left(g'\right))$$
We let
(39) $$\Delta\left(f'\right) = f, \Delta\left(g'\right) = g$$
Thus,
(40) $$\Delta^{-1}(f+g) = \Delta^{-1}(f)+\Delta^{-1}(g)$$
for all $f,g$ given that $f’,g’$ exist. That is, $f$ and $g$ must have defined differences.

Generalizing #

A motivating question #

We are interested in the following question.

Can we find a polynomial that fits a certain given data?

Let us consider the following example. Can we find a quadratic polynomial $f$ such that

(41) $$f(0) = 1, f(1) = 0, f(2) = 5, f(3) = -1~?$$

A motivating question indeed, and the answer is no. Suppose there exists such quadratic polynomial $f$, then

(42) $$\Delta^3 f(x) = 0, \forall x \in \mathbb{R}$$
However, we can check that
(43) $$\Delta^3 f(0) = f(3) - 3f(2) + 3f(1) - f(0) = -17$$

Consider a variant of the question before: Can we find a cubic polynomial $f$ such that

(44) $$f(0) = 1, f(1) = 0, f(2) = 5, f(3) = -1~?$$
The answer is yes! The polynomial
(45) $$-\frac{17}{6}x^3+\frac{23}{2}x^2 - \frac{29}{3}x + 1$$
works. But how do we find this polynomial?

Since

(46) $$\Delta\left(\Delta^2(f(x))\right) = -17$$
(47) $$\Delta^2(f(x)) = -17x + c$$
for some constant $c$. When $x=0$,
(48) $$\Delta^2(f(x)) = 6$$
Hence, $c=6$. Similarly,
(49) $$\Delta^2(f(x)) = -17x+6 \implies \Delta\left(f(x)\right) = -\frac{17}{2}x^2 + \frac{29}{2}x + c'$$
for some constant $c’$. When $x=0$, $\Delta\left(f(x)\right) = -1$. Hence, $c’ = -1$. We could check that
(50) $$\Delta\left(f(x)\right) = \frac{17}{2}x^2 + \frac{29}{12}x - 1$$
, which implies
(51) $$f(x) = -\frac{17}{6}x^3 + \frac{23}{2}x^2 - \frac{29}{3}x + c''$$
When $x=0$, $f(x) = 1$. Hence, $c’’=1$. Thus, the cubic polynomial that fits the given data is
(52) $$-\frac{17}{6}x^3+\frac{23}{2}x^2 - \frac{29}{3}x + 1$$

Can we generalize this? Therefore, we began to ask the following interesting question:

Given the values of $f(0), f(1), \dots, f(n)$, can we find a polynomial $f$ of degree not greater than $n$ that fits this data? Is this polynomial unique?

And the answer is yes to both questions.

Finding a polynomial that passes through $n$ points #

Claim. For any $n,k, i \le k$, we have

(53) $$\Delta^i \binom{n + k}{k} = \binom{n + k}{k - i}$$

We will prove this by induction on $i$. Indeed, this is true for $i = 1$, since

(54) $$\Delta \binom{n + k}{k} = \binom{n +k + 1}{k} - \binom{n + k}{k} = \binom{n + k}{k - 1}$$
Now, fix $n,k$. Suppose this result is true for $i = \ell < k$, Then we will prove that this is true for $i = \ell + 1$.

Indeed,

(55) $$\begin{aligned} \Delta^{\ell + 1} \binom{n + k}{k} &= \Delta \left( \Delta^{\ell} \binom{n + k}{k} \right) \\ &= \Delta \binom{n + k}{k - \ell} \\ &= \binom{n + 1 + k}{ k - \ell} - \binom{n + k}{k - \ell} \\ &= \binom{n + k}{k - \ell - 1} \end{aligned}$$
which proves our assertion.

Every polynomial $P(x)$ can be uniquely represented as

(56) $$\sum_{k} a_k \binom{n + k}{k}$$
for reals $a_k$.

Using this fact, note that if $P(x) \not= 0$, then

(57) $$\begin{aligned} \Delta^{-1}(P(x)) &= \sum_k a_k \Delta^{-1} \left( \binom{n + k}{k} \right) = \sum_k a_k \binom{n + k}{k + 1}\end{aligned}$$

The previous argument proves the existence of such a polynomial passing through $f(0), f(1), f(2), \dots, f(n)$, ensuring the degree is not greater than $n$. In fact, we claim an even more generalized result.

Let $x_1, x_2, \dots, x_n$ be $n$ distinct real values and $y_1, y_2, \dots, y_n$ be $n$ real numbers. Then there exists a unique polynomial $f \in \mathbb{R}[x]$ of degree less than $n$ such that $f(x_i) = y_i$ for $1 \le i \le n$.

Proof #

Proof. We’ll first prove that there exists such polynomial. Consider the polynomial

(58) $$f(x) = \sum_{i = 1}^n y_i \cdot \prod_{i \not= j} \frac{x - x_j}{x_i - x_j}$$
Now, check that $f(x_i) = y_i$ for every $1 \le i \le n$, and we are done. Finally, we will prove uniqueness. Indeed, if there exists two working polynomials $Q,R$ such that
(59) $$Q(x_i) = R(x_i) = y_i$$
for $1 \le i \le n$. Then, either $Q - R = 0$, or $\text{deg} (Q - R) < n$. However, if $Q - R \not= 0$, the polynomial $Q - R$ vanishes at $n$ points, with degree less than $n$, which is a contradiction.